Prototyping of microbial chassis for the biomanufacturing of high-value chemical targets. (30th June 2021) - Robinson, Christopher J.; Tellechea-Luzardo, Jonathan; Carbonell, Pablo; Jervis, Adrian J.; Yan, Cunyu; Hollywood, Katherine A.; Dunstan, Mark S.; Currin, Andrew; Takano, Eriko; Scrutton, Nigel S.
Abstract : Metabolic engineering technologies have been employed with increasing success over the last three decades for the engineering and optimization of industrial host strains to competitively produce high-value chemical targets. To this end, continued reductions in the time taken from concept, to development, to scale-up are essential. Design–Build–Test–Learn pipelines that are able to rapidly deliver diverse chemical targets through iterative optimization of microbial production strains have been established. Biofoundries are employing in silico tools for the design of genetic parts, alongside combinatorial design of experiments approaches to optimize selection from within the potential design space of biological circuits based on multi-criteria objectives. These genetic constructs can then be built and tested through automated laboratory workflows, with performance data analysed in the learn phase to inform further design. Successful examples of rapid prototyping processes for microbially produced compounds reveal the potential role of biofoundries in leading the sustainable production of next-generation bio-based chemicals.